Development and optimization of a resonance-based mechanical dynamic absorber structure for multiple frequencies. Issue 2 (June 2021) - Yoon, Gil Ho; Choi, Hyunggyu; So, Hongyun
This paper presents a new dynamic absorber attenuating the vibrations at three resonance frequencies simultaneously. The dynamic vibration responses of mechanical systems with dynamic absorbers are mainly influenced by how close the eigenfrequencies of the installed dynamic absorbers are to the eigenfrequencies of the hosting structure. To suppress structural vibration at single target frequency, it is enough to install a single mass tuned dynamic absorber whose eigenfrequency is tuned to the excitation frequency. To suppress structural vibrations at multiple frequencies, multiple dynamic absorbers whose eigenfrequencies are tuned differently can be installed. Inevitably this approach increases the total weight of the dynamic absorbers and the manufacturing cost. To overcome the limitation and to attenuate vibrations over a wide range of frequencies, a new dynamic absorber without a damper tuned for multiple frequencies was presented in this research. The present dynamic absorber consists of a mass and two arm-beams connected to a hosting structure. By changing the geometric dimensions, it is possible to precisely tune the eigenfrequencies of the dynamic absorbers to those of hosting structure. The present study also adopts an optimization process to tune the geometric parameters based on the numerical optimization algorithm. With several numerical examples and an experiment, the validity of the present dynamic absorber is presented.